2020
DOI: 10.1007/s40195-020-01123-y
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior and Mechanism of Irradiated 304 Nuclear Grade Stainless Steel in High-Temperature Water

Abstract: Corrosion behavior and mechanism of irradiated 304 nuclear grade stainless steel were studied in simulated pressurized water reactor primary water. The microstructure of the oxide formed on the steel irradiated to different doses over an exposure period range of 25-1500 h was analyzed and compared. It was found that the general and intergranular corrosion rates of the steel were increased with irradiation dose, in correspondence with an evolution of the general oxide and the oxide formed at the grain boundary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Medium-sized particles seemed to grow out of the small particles, and all particles exhibited spinel shapes. Similar spinel particles were identified in many previous experiments involving high-temperature and high-pressure oxidation of 304SS [11][12][13][14][15][16][17]. Figure 1c shows the EDS results for the surface particles shown in Figure 1b, which clearly indicated that the surface particles contained Co and O.…”
Section: Resultssupporting
confidence: 81%
“…Medium-sized particles seemed to grow out of the small particles, and all particles exhibited spinel shapes. Similar spinel particles were identified in many previous experiments involving high-temperature and high-pressure oxidation of 304SS [11][12][13][14][15][16][17]. Figure 1c shows the EDS results for the surface particles shown in Figure 1b, which clearly indicated that the surface particles contained Co and O.…”
Section: Resultssupporting
confidence: 81%